Pastoral “Kotew" bagi Umat Paroki St. Petrus Kanisius Kandui, Palangka Raya (Sebuah Telaah Teologis berdasarkan Teologi Kontekstual Stephen B. Bevans) - Eugenius Ervan Sardono; Lorensius Fura; Kristoforus Ganordin; Antonius Denny Firmanto (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
The purpose of this research is to explore the fundamental aspects of catechesis among the people. It turns out that homily or preaching can be absorbed inadvertently if the pastoral team promotes "Kotew" spirituality. “Kotew” in the Manyaan and Tewoyan Tribes, Kandui, Central Kalimantan is defined as “stopping by” or “hanging out”. Bevans, a contextual theologian looking at one's understanding of God's Revelation, one's attitude to human experience, one's understanding of the normativity of Scripture or tradition, one can choose to enter into a critical dialogue between the past and the present in his opinion. This study finds out that "Kotew" needs to be promoted among the pastoral workers of St. Peter Canisius parish in Kandui. When sermons, meditations, lectures deep in meaning just stop at the altar, people of Kandui feel the “warmth of brotherhood” brought by “Kotew”. The main context of the research is the parishioners of St. Peter Canisius, Kandui. Mission development, both in terms of quantity and quality, continues at St. Peter Canisius, Kandui. This parish just became an independent parish in 2013. The SMM congregation was entrusted by the Bishop of Palangka Raya to open the mission there. This parish was already prepared to become a parish in 1999. However, administratively and independently, Kandui only became a parish in 2013. The methodology used by the author in this paper is a qualitative method, namely phenomenology. These research’s sources are the lives of faith of the believers.